RE-READING PARETO ON ELITE POWER AND SOCIETAL BIPOLARISATION a critical perspective on... metapolitics and democracy. - Marshall, Alasdair J. 1968- (ROUTLEDGE, 2026)
Assessing Vilfredo Pareto's sociological reworkings of Machiavelli's Fox and Lion animal spirits as friend-enemy codings, this book offers a unique insight into the growing division today between relatively liberal elites and relatively conservative non-elites.Re-Reading Pareto on Elite Power and Societal Bipolarisation utilises key ideas common to Pareto's elite theory, general sociology and theory of demagogic plutocracy, and fleshes out a unique perspective for making sense of contemporary societal bipolarisation in terms of friend-enemy codings. The first part of the book explores what Pareto's core ideas are and outlines why they matter today. The second part considers how we might elaborate and apply Pareto's concept of 'open elites' to reverse contemporary societal bipolarisation and build safer and more mature democracies. The third part explains how we can apply Pareto to predict further deterioration towards fundamental social conflict - such that Pareto's sociological imagination becomes risk imagination we desperately need today.For academics and students across the domains of sociology, political science and social science in general, the book warns of widespread elite-institutional bias in their research and points to Pareto's neutral and balanced approach as a corrective - offering a uniquely Paretian view of minimal criteria for democracy, as well as a uniquely balanced analytical perspective for making sense of our 'culture war'.
Keywords: Pareto, Vilfredo, -- 1848-1923.; Economics -- Philosophy.; Sociology -- Philosophy.; Elite (Social sciences); elektronické knihy; electronic books